The prognostic value of the p53 gene expression and mutation in ovarian cancer (Faculty of Medicine Universitas Indonesia, 2009)
Aim This study aimed to observe the role of the p53 gene in ovarian carcinogenesis, and identify the prognostic significance of the expression of the p53 protein expression in ovarian cancer. Methods Fourty one ovarian cancer patients were examined in this study by analyzing the mutations of p53 gene from their blood samples, and by analyzing the p53 protein expression from ovarian cancer tissues. Results Mutational analysis in